Studi Inhibisi Korosi Baja oleh Ekstrak Biji Kakao (Theobroma cacao) dalam Medium Udara - Indah Muspita; Irma Mon; Yerimadesi Yerimadesi (Jurnal Periodic Jurusan Kimia UNP, 2012)
Steel very easily have corrosion in the air (atmosphere corrosion), this led to the decline of quality steel. Therefore, Inhibition of steel Corrosion Study performed by the extract of Cocoa (Theobroma cacao) in the Medium of air which aims to look at the influences of the cocoa seed extract inhibition of corrosion of steel in the medium of air.This research uses a method of reduction of weight (weight loss), identification of compound steel absorbed on the surface of steel using a FTIR spectrometer, analysis of the steel surface and done using stereo microscopes. Of research results obtained that the cacao seed extract may decrease the rate of corrosion of steel in the air with corrosion inhibition efficiency 89,46%. Increased efficiency due to the lack of inhibition adsorption on cocoa extract steel surface that has been evidenced by the results of the FTIR. Surface analysis of steel with a microscope shows the difference of surface state of specimens not coated and coated cocoa extract solution.